Corporate Social Responsibility Disclosure: A Study of Islamic banks in Malaysia and GCC Countries - Shukor Harun, Mohd; Ridhwan Ab. Aziz, Muhammad; Nazri Mohd Noor, Mohd (International Journal of Engineering and Technology, 2018)
The primary aims of this research is to investigate the CSR disclosure practice among Islamic banks in Malaysia and GCC. In fulfilling the research aims, annual reports of GCC Islamic banks for the period 2013 have been analyzed using manual content analysis; which involves 9 observations. The CSR disclosure index is constructed based on 12 dimensions using AAOIFI standard no 7, 2010. The analysis shows a low level of average CSR disclosure (46%) than expected. Whereas, the highest level of CSR disclosure score is 67% and the lowest is 25 %.among the sample Islamic banks. The current study suggests that there is a need for improving the current CSR disclosure practice in GCC Islamic banks by imposing additional constraints on the banks management to increase the level of awareness regarding to CSR disclosure issues. The findings provide an important implication to the body of knowledge, as they pave the ways for further investigation in CSR practices among Islamic banks. Itâ€™sÂ also provide an important implication for AAOIFI as a regulatory body to enhancing the CSR disclosure practice among Islamic banks, and at the same time remain competitive in the global banking industry.Â Â